PENGEMBANGAN LKPD BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) PADA MATERI NORMA KELAS VI SDN 139 PEKANBARU - Dhea Aprilia Caroline Siregar; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop student worksheets based on Higher Order Thinking Skills for the “Social Norms” unit in sixth-grade elementary school and to describe the validity level of the resulting product. The study employed the Research and Development method using the ADDIE model, limited to the Analysis, Design, and Development stages. The research was conducted at SDN 139 Pekanbaru, involving six validators consisting of two subject matter experts, two language experts, and two design experts. Data were collected through interviews and validation questionnaires. The data analysis techniques used included qualitative analysis of interview results, suggestions, and comments from the validators, as well as quantitative analysis using percentage calculations to determine the product’s validity level. The results of the study indicate that the developed product consists of student worksheets based on Higher Order Thinking Skills for the “Norms” curriculum, which include activities involving analysis, evaluation, and creation. The validation results show that the content aspect scored 89.99%, the language aspect 96.11%, and the design aspect 95.29%, with an overall average of 93.79%, which falls into the “highly valid” category. Thus, the developed product is deemed suitable for use as supplementary teaching material for Pancasila education in elementary schools